PENDAHULUAN TINGKAT KEBUGARAN FISIK DENGAN SIX MINUTE WALK TEST PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TARUMANAGARA - Gunalam, Irene Fransisca; Lontoh, Susy Olivia (Ebers Papyrus, 2021)
out a person's work capacity, we must determine the maximum oxygen (O2) consumption or VO2 max. Physical fitness is the ability and physical endurance of a person in carrying out various daily activities, without experiencing fatigue. Research related to the level of physical fitness is a preliminary study because this study aims to determine the level of physical fitness of students of the Tarumanagara University Faculty of Medicine using a six minute walk test. This research can be developed and can predict the level of physical fitness in young adults. The research conducted was an experimental analytical research. The research subjects were active medical students aged 18-22 years, willing to sign an informed consent and were physically and mentally healthy. The study was conducted on 44 subjects and subject was taking by judgmental sampling. Subject data consisted of age, gender, measurement results of body weight, height, blood pressure, pulse and VO2 Max before and after doing the six minute walk test and the distance after doing the six minute walk test. The level of physical fitness with a six minute walk test among students of the Faculty of Medicine at Tarumanagara University varied the results, most of them showed poor results and women were more dominant with poor fitness levels. The decrease in VO2 max before and after doing the six minute walk test and this result is in accordance with the results of the poor physical fitness level of the Tarumanagara University medical faculty students.